2021
DOI: 10.1021/acs.energyfuels.1c03254
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2O of Gas-Bearing Shale in Its Physicochemical Properties and CH4 Adsorption Performance Alteration Due to Microwave Irradiation

Abstract: Microwave irradiation is available to produce shale gas. Practical gas-bearing shale reservoirs often contain water (H2O). Given the special physicochemical property of H2O and its occurrence rule in the gas-bearing shale matrix, the presence of H2O has potential effect on electromagnetic energy penetration and dielectric property of the shale matrix, therefore affecting application of microwave irradiation to produce the chief component of shale gas, that is, methane (CH4), from the shale reservoir. Hence, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
(150 reference statements)
0
9
0
Order By: Relevance
“…Shale gas reservoirs always contain water, including bound water on the surface of matrix pores and free water in pore-fractures. 7,114,115 Water molecules fill the effective pores and separate the effective pores into multiple invalid pores (refers to the pores with diameter less than the dynamic diameter of CH 4 ), which significantly reduce the number of effective pores and increase the number of invalid pores correspondingly. 116−118 H 2 O molecules are mainly adsorbed on clay mineral particles and pore surfaces through hydrogen bonds and surface forces, form an adsorbed water film, occupy the adsorption site, and hinder the adsorption of CH 4 molecules.…”
Section: Numerical Simulation Of Chmentioning
confidence: 99%
See 2 more Smart Citations
“…Shale gas reservoirs always contain water, including bound water on the surface of matrix pores and free water in pore-fractures. 7,114,115 Water molecules fill the effective pores and separate the effective pores into multiple invalid pores (refers to the pores with diameter less than the dynamic diameter of CH 4 ), which significantly reduce the number of effective pores and increase the number of invalid pores correspondingly. 116−118 H 2 O molecules are mainly adsorbed on clay mineral particles and pore surfaces through hydrogen bonds and surface forces, form an adsorbed water film, occupy the adsorption site, and hinder the adsorption of CH 4 molecules.…”
Section: Numerical Simulation Of Chmentioning
confidence: 99%
“…Merkel et al and Li et al suggested that the adsorption capacity of H 2 O in shale is stronger than that of CH 4 and that the CH 4 adsorption amount can be reduced by 80%–90% in the presence of water. Shale gas reservoirs always contain water, including bound water on the surface of matrix pores and free water in pore-fractures. ,, Water molecules fill the effective pores and separate the effective pores into multiple invalid pores (refers to the pores with diameter less than the dynamic diameter of CH 4 ), which significantly reduce the number of effective pores and increase the number of invalid pores correspondingly. H 2 O molecules are mainly adsorbed on clay mineral particles and pore surfaces through hydrogen bonds and surface forces, form an adsorbed water film, occupy the adsorption site, and hinder the adsorption of CH 4 molecules. When the water content is higher than 4 wt %, the CH 4 adsorption capacity in shale decreases significantly. Water molecules are also present in the pore structure of kerogen, but it is generally suggested that the structure of organic matter is hydrophobic, so its water content is significantly lower than that in the pores of clay minerals. …”
Section: Influence Of Clay Content On Ch4 Adsorption Capacity In a Sh...mentioning
confidence: 99%
See 1 more Smart Citation
“…33 Studies have shown that the CH 4 adsorption capacity of coal is proportional to the content of aromatic groups. 34 The adsorption heat generated by the adsorption of CH 4 on coal is proportional to the content of oxygen-containing functional groups in its molecular structure. 35 The number of methyl and methylenes is proportional to the adsorption potential well of coal for CH 4 .…”
Section: V P P Pmentioning
confidence: 99%
“…Zhang et al. [ 15 ] fabricated MOF‐derived hollow Co 3 O 4 nanocages to construct a hybrid SC device. Nevertheless, the diffusion‐controlled faradaic reactions continue to influence their reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%